A Distributed Public Key Infrastructure Based on Threshold Cryptography for the HiiMap Next Generation Internet Architecture - Oliver Hanka; Michael Eichhorn; Martin Pfannenstein; Jörg Eberspächer; Eckehard Steinbach (Future Internet, 2011)
In this article, a security extension for the HiiMap Next Generation Internet Architecture is presented. We regard a public key infrastructure which is integrated into the mapping infrastructure of the locator/identifier-split addressing scheme. The security approach is based on Threshold Cryptography which enables a sharing of keys among the mapping servers. Hence, a more trustworthy and fair approach for a Next Generation Internet Architecture as compared to the state of the art approach is fostered. Additionally, we give an evaluation based on IETF AAA recommendations for security-related systems.